Dendritic/Post-synaptic Tau and Early Pathology of Alzheimer’s Disease - Yin, Xiaomin; Zhao, Chenhao; Qiu, Yanyan; Zhou, Zheng; Bao, Junze; Qian, Wei (Frontiers in Molecular Neuroscience, 2021)
Microtubule-associated protein tau forms insoluble neurofilamentous tangles (NFT) as one of the major histopathological hallmarks of Alzheimer’s disease (AD). Studies have emphasized that tau causes early functional deficits much before neurofilamentous aggregates develop. The redistribution of tau from the axon into the somatodendritic compartment of neurons and dendritic spines causes synaptic impairment, and then leads to the loss of synaptic contacts which correlates better with cognitive deficits in AD than amyloid-β (Aβ). In this review we discuss the underlying mechanisms by which tau mislocalizes to dendritic spines and contributes to synaptic dysfunction in AD. We also review the synergistic effect of tau and oligomeric forms of Aβ on promoting synaptic dysfunction in AD.